Training of trainers in basic sex education - O. Fernández-García; M.D. Gil-Llario; R. Ballester-Arnal; J. Castro-Calvo (INFAD, 2017)
Introduction: The training of future sexual educators requires not only a high degree of specialization, but also the mastery of a series of skills and competences since it requires a constant adaptation to the characteristics of the target group. The training of these educators, beyond fulfilling the objective of providing specific knowledge, must ensure the perceived mastery of the skills to carry out different intervention formats according to the size and characteristics of the target group as well as the time and the objectives pursued. In order to achieve these objectives, a work proposal has been devised that provides varied experiences, maximizing the teaching time. Method: In this experiment 25 students enrolled in the subject “Prevention of unsafe sex practices” of the official master’s degree in Psychological Intervention in the Social Area of the University of Valencia, who were administered both at the beginning and at the end of the course An instrument developed ad hoc that evaluated the degree of knowledge, self-efficacy and perception of competence in the field of affective-sexual education. Results: The proposal has been positively valued not only in terms of increasing knowledge and skills, but also and especially in terms of perception of self-efficacy and competence of future educators. Thus, the percentage of those who after the course considered that they had enough knowledge to design an autonomous program of affective-sexual education and that had strategies for their implementation was 72% and 60% respectively (compared to 0 % and the initial 12%). Conclusions: This methodological proposal of training of trainers has proved effective in increasing not only the theoretical knowledge about the design of programs of affective-sexual intervention, but also the perception of self-efficacy in its implementation in any group and context.